Inconsistency of chi2 test for sparse categorical data under multinomial sampling - Samusenko, Pavel (Lietuvos matematikos rinkinys, 2011)
Simple conditions for the inconsistency of Pearson’s chi2 test in case of very sparse categorical data are given. The conditions illustrate the phenomenon of “reversed consistency”: the greater deviation from the null hypothesis the less power of the test.